Introgression of lineage c honey bees into black honey bee populations: a genome-wide estimation using single nucleotide polymorphisms (SNPS) - Henriques, Dora (2013)
The black honey bee, Apis mellifera mellifera L., is probably the honey bee subspecies more threatened by introgression from foreign subspecies, specially lineage C A. m. carnica and A. m. ligustica. In fact, in some areas of its distributional range, intensive beekeeping with foreign subspecies has driven A. m. mellifera populations to nearly replacement. While massive and repeated introductions may lead to loss of native genetic patrimony, a low level of gene flow can also be detrimental because it may compromise honey bee survival and local adaptation by disrupting co-evolved gene complexes. Assessing levels of introgression is an important activity in breeding programs, especially when conservation of native races is a major concern. Previous surveys of A. m. mellifera populations estimated the introgression of lineage C honey bees by using mtDNA and microsatellites markers. In this presentation we used both mtDNA (sequence data of the tRNAleu-cox2 intergenic region) and over 1245 SNPs to ascertain introgression levels of A. m. carnica and A. m. ligustica in A. m. mellifera populations (some included in conservation programs) sampled in France, Switzerland, Denmark, Holland, Norway, England, and Scotland. We used different model-based approaches, implemented by different software applications (Structure, Admixture, NewHybrids). We found varying levels of introgression ranging from less than 3% (in Norway) to over 65% (in France).